Status Gizi dan Paparan Media Elektronik Terhadap Usia Menarche Siswi Kelas VII SMP 55 Palembang Tahun 2017 - Melia Rahma; Ghauri (LPPM STIKES Al-Ma'arif Baturaja, 2018)
Menarche is the first period of menstruation that is the hallmark of a healthy and non-pregnant woman. Factors that influence the age of menarche are internal factors in the form of genetic factors and nutritional status and external factors in the form of social economy, nutrition, and exposure of electronic media and lifestyle. The purpose was to know the relationship of nutritional status and exposure of electronic media to the age of menarche students of class VII SMP N 55 Palembang Year 2017. This research uses an analytical survey method with a cross-sectional approach with a chi-square statistical test. This research was conducted in May of 2017. Population was taken from all students of class VII at SMP N 55 Palembang with sample 125 respondents. The data were analyzed by univariate and bivariate analysis. There is a relationship of nutritional status to age menarche with ρ value 0.003 ≤ 0.05 which shows there is a significant correlation between nutritional statuses to menarche age. And there is a relationship of exposure of electronic media to the age of menarche with ρ value 0,001 ≤ 0.05 which shows there is a significant relationship between exposures of electronic media to the age of menarche. From the results of this research which have been done show that there is a relation between nutritional status and exposure of electronic media against the age of menarche grade VII SMP N 55 Palembang in 2017.